2-Bromo-3-phenyl-1-(3-phenylsydnon-4-yl)prop-2-en-1-one - Goh, Jia Hao (International Union of Crystallography, 2010)
The title sydnone derivative [systematic name: 2-bromo-1-(5-oxido-3-phenyl-1,2,3-oxadiazolium-4-yl)-3-phenylprop-2-en-1-one], C(17)H(11)BrN(2)O(3), exists in a Z configuration with respect to the acyclic C=C bond. An intramolecular C—H⋯Br hydrogen bond generates a six-membered ring, producing an S(6) ring motif. The 1,2,3-oxadiazole ring in the sydnone unit is essentially planar [maximum deviation = 0.011 (2) Å] and forms dihedral angles of 55.39 (13) and 57.12 (12)° with the two benzene rings. In the crystal structure, intermolecular C—H⋯O hydrogen bonds link molecules into two-molecule-thick arrays parallel to the bc plane. The crystal structure also features a short intermolecular N⋯C contacts [3.030 (3) Å] as well as C—H⋯π and π–π interactions [centroid–centroid distances = 3.3798 (11) and 3.2403 (12) Å].